Assessing the forestry environmental condition using GIS-AHP approach in the Forest Research Institute Malaysia (FRIM) Campus, Malaysia - Asmawi, M. Zainora; Ngaimin, Najihah; Mahamod, Nor Zalina; Omar, Hamdan; Hj. Mohd. Noor, Norzailawati (2016)
Degradation of environmental forestry condition has become a serious issue faced by many countries today. The primary cause of this problem is related to human disturbance towards natural resources. Therefore, the concern of this research is to assess the level of the health condition of artificial and naturally regenerated forestry area in FRIM campus, consisting of 54 fields, to see how best it can contribute in balancing the ambient of air quality. For data collection, this research depends on a series of GIS database covering five criteria, namely slope, altitude, crown diameter, tree height and carbon stock. These data were analysed using Analytic Hierarchy Process (AHP) that produced the composite map, classifying the site as the healthiest, moderately healthy and less healthy condition. The results indicate that most of the forested areas in FRIM campus lie under the category of healthiest condition with 45.5% in the area of 220.8 hectares whereby the key contributor is the carbon stock. Relating these criteria for ecosystem health will be beneficial toward monitoring forest change in landscapes undergoing rapid development.